Analysis of the distribution of budgetary resources allocated to the training of human talent, of the officials of the Special Administrative Unit Migration Colombia, 2018 to 2019 (2019)
This paper aims to analyze the distribution of budgetary resources allocated to the training and generation of a culture of learning of human talent, of the officials of the Special Administrative Unit Migration Colombia, in the periods of 2018 and 2019. The generation of learning culture includes, subsidies granted to officials to pay their university fees and, courses, trainings, workshops, etc. offered directly by Migración Colombia for some officials, depending on the need of knowledge of each official according to the agency in which they work. The idea is to analyze the execution of the budget approved by the Ministry of Finance and public credit is sufficient and if it is being executed correctly, according to the needs of the entity.